Lessons Learned Framework for Efficient Delivery of Construction Projects in Saudi Arabia (Construction Economics and Building, 2021)
The Kingdom of Saudi Arabia (KSA) has the largest construction market in the gulf region. Nevertheless, the sector faces issues related to inefficiency and ineffectiveness in project delivery. This research aims to explore the impact of current practices across projects lifecycles, and to utilize findings to develop an integrated strategic construction project management framework (ISCPMF) that may pave the way to efficient and effective project implementation. To achieve this objective, the authors have traced the implementation processes of nine projects for data collection. This was based on a deductive approach with preconceived themes. Within-case and cross-case analysis was conducted. The data was complemented by holding three separate focus-group discussions with a total of nineteen participants, and the initial findings were cross-checked with six experts. The deficiencies that surround the pre-construction phase and disconnected activities that are carried out in different timespans represent the first barrier to implement projects successfully. This is coupled with low capacities contractors and non-proactive construction teams that lack a management toolbox to alleviate accumulated issues and control project progress. The unavailability of infrastructure and utilities did not ease construction nor made inspection possible, which led to late occupancy of facilities, waste of resources and failure to deliver the desired benefits effectively. The adoption of ISCPMF will institutionalize and bridge project phases. This may play a vital role in implementing projects efficiently and effectively and building data to benefit future projects. Though the research is limited to higher education facilities, the findings may be generalized to public construction projects.